2018
DOI: 10.1098/rstb.2018.0133
|View full text |Cite
|
Sign up to set email alerts
|

Developmental perspectives on risky and impulsive choice

Abstract: Epidemiological data suggest that risk taking in the real world increases from childhood into adolescence and declines into adulthood. However, developmental patterns of behaviour in laboratory assays of risk taking and impulsive choice are inconsistent. In this article, we review a growing literature using behavioural economic approaches to understand developmental changes in risk taking and impulsivity. We present findings that have begun to elucidate both the cognitive and neural processes that contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 179 publications
(220 reference statements)
3
40
0
1
Order By: Relevance
“…Third, our focus on self-regulatory ability as an explanatory factor between conflict and risk behavior is both consistent with research on adolescent vulnerability to engagement in risk behaviors as well as offers potential strategies by which to reduce risk for poor psychosocial outcomes in situations of decision-making under stress, which we will discuss. The features of our study-experimental, multiple levels of analysis that include physiology and behavior-are consistent with those recently recommended to identify cognitive and emotional factors that contribute to adolescent decision-making (Rosenbaum and Hartley 2019).…”
Section: Main Findingssupporting
confidence: 63%
“…Third, our focus on self-regulatory ability as an explanatory factor between conflict and risk behavior is both consistent with research on adolescent vulnerability to engagement in risk behaviors as well as offers potential strategies by which to reduce risk for poor psychosocial outcomes in situations of decision-making under stress, which we will discuss. The features of our study-experimental, multiple levels of analysis that include physiology and behavior-are consistent with those recently recommended to identify cognitive and emotional factors that contribute to adolescent decision-making (Rosenbaum and Hartley 2019).…”
Section: Main Findingssupporting
confidence: 63%
“…Given the many novel contexts that adolescents encounter during their transition toward parental independence 46,47 , a reduced Pavlovian bias might facilitate exploration and unbiased evaluation of action values, allowing adolescents to approach uncertain or ambiguous situations to discover their true value 48 . However, such willingness to continue sampling in stochastic environments that may yield negative outcomes may contribute to a seemingly heightened willingness to take risks during this developmental stage 49,50 . Pavlovian responses serve critical survival functions 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…First, the results provide additional evidence that SRPs are at best weakly related to cognitive abilities, as previously shown by Frey et al () but in contrast to the results of Dohmen et al (2010). It has also been debated whether impulsiveness and age has a direct effect on risk preferences, or whether their influence is indirect, through cognitive abilities (see, e.g., Mata et al, ; Rosenbaum & Hartley, ). On basis of the location in the network, our results support the notion that the influence of impulsiveness and age is indirect, hence supporting a view that specific task characteristics, such as learning and computational demands, will interact with these variables to produce an effect on the behaviorally elicited risk preference.…”
Section: Discussionmentioning
confidence: 99%
“…First, SRPs seem to show both higher test–retest stability and convergent validity relative to RRPs (Frey et al, ; Mata, Frey, Richter, Schupp, & Hertwig, ; Pedroni et al, ). Second, there exists strong evidence for a relation between SRPs and personality measures (e.g., Big‐5 traits; Frey et al, ; Mata et al, ; Nicholson et al, ), and although some studies have documented a relation between RRPs and personality measures such as impulsiveness (Demaree, DeDonno, Burns, & Everhart, ; Demaree, DeDonno, Burns, Feldman, & Everhart, ; Rosenbaum & Hartley, ), others have failed to identify such a link (Frey et al, ) or only found low degrees of association (Becker, Deckers, Dohmen, Falk, & Kosse, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation